Microsatellite analysis to evaluate the seedling and maturation of Elaeis guineensis populations - Hayati, Rahmah; Lisnawita, Lisnawita; Munir, Erman; Basyuni, Mohammad (Kuwait Journal of Science, 2021)
To conduct efficient disease screening, the differentiation of the Elaeis guineensis to Ganoderma resistance populations is critical. Differentiation can be done by analyzing the genetic structures of the two populations and comparing their seedling and matures. This article presents the results studying four selected stably amplified polymorphic of codominant microsatellite data to estimate the differentiation between eight E. guineensis populations from different types of inoculated or symptoms of Ganoderma from North Sumatera, Indonesia. The DNA extraction was carried out based on the CTAB protocol with a little modification. The forward and reverse primers, i.e., P4(EGIFR), P6(EG01), P7(EG02), and P9(EG03) were used in polymerase chain reaction (PCR). The detection of the results of amplification was performed using molecular weight analysis on UVITEC-1D software. To determine the microsatellite analysis, the data of genes were used to perform with the GENALEX ver 6.502 and MVSP ver 3.2 software. Four of the loci have polymorphism for all types of seedling and mature species of E. guineensis. The polymorphism information content was calculated as PIC=0.70. In addition, this represents a great extent of genetic structure. The analysis of variance (AMOVA) showed significant (5%) differentiation among individuals (100%) between eight types of population. A final clustering by UPGMA analysis, based on squared Euclidean and Datalog (10), transformed genetic distances and revealed a significant difference clusters in seedling and mature in the populations.